REGIONAL HEALTH-SAVING CENTRE IN EDUCATION - Elena Nikolayevna Pozharskaya (Advanced Engineering Research)
The development of “new technologies, mechanisms and regulations of monitoring and saving health of schoolchildren” is determined as one of the priority directions of the Russian education development in “Our new school” national educational strategy. The pilot project of the Ministry of General and Vocational Education of the Rostov Region is directed to creating a global health-saving educational space in the Rostov Region. The focal point of the pilot project is the Regional health-saving centre operation in the educational sphere of the Rostov Region. It is the first health-saving centre at the regional level in the Russian Federation. It acts as a coordinating centre for health-saving schools in the Rostov Region to solve a number of tasks: organization, monitoring, methodic, expert, information ones. Establishing the Regional health-saving centre in education propels the Rostov Region to the top in the sphere of the health-saving pedagogics.